How to Manage the Big Bang… Evolution or Revolution in the Introduction of an MLE? - Quinsee, Susannah; Sumner, Neal (Proceedings of the International Conference on Networked Learning, 2004)
This paper examines how introducing an institution-wide managed learning environment impacts on the processes of organisational change. City University is used as a case study - interviews with leading members of the institution providing an exemplar of the change process and institutional plans for a future strategy.